2019
DOI: 10.1007/s11306-019-1579-1
|View full text |Cite
|
Sign up to set email alerts
|

The HDL lipidome is widely remodeled by fast food versus Mediterranean diet in 4 days

Abstract: Introduction: HDL is associated with increased longevity and protection from multiple chronic diseases. The major HDL protein ApoA-I has a half-life of about 4 days, however, the effects of diet on the composition of HDL particles at this time scale have not been studied. Objectives: The objective of this study is to investigate the short term dietary effect on HDL lipidomic composition. Methods: In this randomized order cross-over study, ten healthy subjects consumed a Mediterranean (Med) and a fast food (FF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
4
21
0
1
Order By: Relevance
“…HDL lipidome is modulated by diet, even by a short-time dietary intervention. After two 4-day dietary interventions, HDL lipidome was widely modulated and fatty acids contained in HDL phospholipids were the most variable lipids by diet [17]. The 4-day MD intervention increased the quantity of phosphatidylcholine with very long chain and double bonds fatty acids, compared to baseline and to the 4-day fast food diet intervention.…”
Section: Hdl Compositionmentioning
confidence: 96%
See 3 more Smart Citations
“…HDL lipidome is modulated by diet, even by a short-time dietary intervention. After two 4-day dietary interventions, HDL lipidome was widely modulated and fatty acids contained in HDL phospholipids were the most variable lipids by diet [17]. The 4-day MD intervention increased the quantity of phosphatidylcholine with very long chain and double bonds fatty acids, compared to baseline and to the 4-day fast food diet intervention.…”
Section: Hdl Compositionmentioning
confidence: 96%
“…Otherwise, after the interventions, Hernaez et al, 2019, made an evaluation of foods consumed by 196 individuals from the initial study population, in order to create different groups [13]. Individuals in each study population were different between studies, healthy individuals were included in a total of 5 study populations [15][16][17][18][19], and the rest of the study populations included high cardiovascular risk individuals, which suffered from dyslipidemia, obesity or hypercholesterolemia [13,14,[20][21][22][23][24][25]. Intervention time varied between studies.…”
Section: Comparison Between Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The half-life of ApoA-I, the main 4 protein constituent of HDL, is approximately 4 days, 19 and we previously showed that the HDL lipidome is drastically remodeled by diet in 4 days. 20 Hence, we postulated that if there is an effect of diet on HDL glycoprofiles it may be visible within this time frame.…”
Section: Introductionmentioning
confidence: 98%